2007
DOI: 10.1111/j.1365-2591.2007.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Accidental ingestion and aspiration of root canal instruments and other dental foreign bodies in a French population

Abstract: The incidence of ingestion or aspiration of endodontic instruments was low even thought most general practitioners do not routinely use rubber dam. Use of rubber dam by general practitioners for endodontic procedures should be encouraged by stressing its advantages rather than the fear factor of accidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 24 publications
1
74
0
9
Order By: Relevance
“…14 In relation to the lack of use of rubber dam in endodontics, considering the risk for the patient of inhalation and ingestion of root canal instruments, 15 strict guidelines should be issued by all relevant standard setting and where appropriate, regulatory bodies, with full compliance across the spectrum of clinical practice.…”
Section: Rubber Dammentioning
confidence: 99%
“…14 In relation to the lack of use of rubber dam in endodontics, considering the risk for the patient of inhalation and ingestion of root canal instruments, 15 strict guidelines should be issued by all relevant standard setting and where appropriate, regulatory bodies, with full compliance across the spectrum of clinical practice.…”
Section: Rubber Dammentioning
confidence: 99%
“…1,2 Susini et al reported the incidence of aspiration for endodontic instruments was 0.001 per 100,000 root canal treatments and the incidence of ingestion was 0.12 per 100,000 root canal treatments. 4 The majority of ingested foreign bodies pass through the gastrointestinal tract without any signs and symptoms. However, coughing, gagging, dysphagia, odynophagia, nausea and vomiting may occur.…”
Section: Discussionmentioning
confidence: 99%
“…9,30 The importance of safety of rubber dam is highlighted by the list of endodontic instruments that have been ingested or inhaled. 7 The record of two insurance companies were examined by Susini et al 8 This represented 24,651 French dentists over 11 years period and found that the incidence of aspiration or ingestion of endodontic instruments was quite low i.e 0.001 per 100,000 and 0.12 per100,000 root canal treatments respectively. Despite this, doing root canal treatment without the use of rubber dam is harmful for the patient and it is considered legally indefensible.…”
Section: IVmentioning
confidence: 99%
“…As rubber dam acts as a protective shield in the working area, therefore it protects inhalation and swallowing of dental materials, fine instruments, tooth fragments and irrigants into the patient , s orophyranx. 7,8 Many societies in the world recommend the use of rubber dam in many dental procedures, including the European Society of Endodontology 9 and British Society of Paediatrics Dentistry. But inspite of all the known advantages of rubber dam, the majority of dentists do not always use a rubber dam during operative and endodontic procedures.…”
Section: Introductionmentioning
confidence: 99%